What Factors Moderate the Relationship between Job Embeddedness and Turnover Intention, Organizational Citizenship Behavior and Employee Performance - Leiyun, Ren (2022)
Employee turnover is a persistent challenge for all businesses in today's highly competitive economy, as employees are an organisation's most valuable asset. Employee turnover, particularly when critical employees depart, will result in considerable financial losses for the business. As the largest component of the labour force, Generation Y has been proved to have a high turnover rate and turnover tendency (Lee et al., 2018). To shed light on why some millennial employees consider leaving their employers while others do not, based on the original model theory of job embeddedness, this paper examines the moderating effects of job alternatives, individualism-collectivism, risk aversion, gender, household registration and contractual nature on the relationship between job embeddedness and turnover intention and work-related outcomes. Primary data are collected via questionnaires from the target group of Chinese millennials. According to the collected and analysed results, it is found that the view that job embeddedness can well predict turnover intention is also applicable to Chinese millennials. The findings also show that job alternatives, individualism-collectivism, risk aversion, and gender can act as moderators in the relationship between job embeddedness and turnover intention, organisational citizenship behaviour and employee performance. Taken together, these findings suggest that individuals can be embedded differently and react differently to embedded perceptions. Based on these findings, an employee retention framework incorporating risk aversion, job alternatives, individualism-collectivism, as well as gender retention strategies are conceptualised and recommended to human resource practitioners in the operations and development industries to optimise their millennial employee retention.